Peran Masjid Istiqlal Osaka Jepang bagi Masyarakat Pekerja Migran Indonesia - Natsir, Imron (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
The research focuses on the role of the Istiqlal Mosque in Osaka (MIO) for Indonesian migrant workers in Japan, by applying qualitative methodology. Through in-depth interviews and participatory observations, the study explores how MIO meets the religious and social needs of the Indonesian migrant community. Research findings suggest that the MIO acts not only as a place of worship, but also as a community centre that provides emotional, social, and cultural support. The mosque plays a central role in the well-being and integration of migrant workers in their new neighborhoods. The study confirms the importance of religious institutions in providing support to the migrant population and encourages further research to understand similar dynamics in other migrant communities. The study provides in-depth insight into the relevance of the mosque in preserving the religious and cultural identity of the diaspora, as well as its contribution to the overall well-being of the Indonesian migrant community in Japan.